Vine dance, Hungarian dancing, Federation Square, Melbourne, 29 October 2006 - Gordon-Brown, Susan (2006)
2006 was the 50th Anniversary of the Hungarian Uprising. Celebrations held at Federation Square were part of the commemorations.
Title supplied by photographer.
Acquired in digital format; access copy available online.
Mode of access: Internet via World Wide Web
Purchased from Susan Gordon-Brown, 2007.
Keywords: Folk dancing, Hungarian -- Victoria -- Melbourne -- Photographs; Ethnic costume -- Victoria -- Melbourne -- Photographs; Hungary -- Australia -- Photographs; Dancers -- Hungary -- Victoria -- Melbourne -- Photographs; Federation Square (Melbourne, Vic.) -- Photographs